The German Epidemiological Hemodialysis Itch Study (GEHIS): 10-year follow-up of pruritus and health-related quality of life in patients on haemodialysis - Bentz, Philipp; Kaplan, Mustafa; Simontowsky, Lara; Weisshaar, Elke (British journal of dermatology, 2025)
Dear Editor, Even in the face of new treatments, chronic pruritus (CP) (itch ≥ 6 weeks) in patients on haemodialysis (HD) is a phenomenon that is difficult to control. While some drugs, such as difelikefalin, showed promising results1 in the reduction of CP, others failed.2 The German Epidemiological Hemodialysis Itch Study (GEHIS) is a representative, prospective cross-sectional observational cohort study of 860 patients on HD, which began in 2013. It addresses the prevalence and associated factors of CP in patients on HD, such as health-related quality of life (HRQOL).In 2017, a follow-up study was performed.3 The remaining 376 patients were contacted as part of a 10-year follow-up, which began in 2023. The HD units (HUs) were asked about the patients’ status (alive/deceased, renal transplant, change of HU) and recent legal address. One HU had closed, and therefore no information could be obtained for nine patients. As previously signed informed consent included contacts for follow-up surveys, patients then received a questionnaire on sociodemographic data, sleep and comorbidities, the Short Form (SF)-12 Health Survey and Hospital Anxiety and Depression Scale (HADS). If CP was reported, patients were asked to complete a second questionnaire with details on location, sensation and severity of CP and the therapy used. HRQOL was assessed using the ItchyQoL questionnaire.